The roots of ethnic conflicts in the Balkans - Swoboda, Wincenty (Balcanica Posnaniensia. Acta et studia, 2001)
The author presents the historical origins of nationality conflicts in the Balkans, arguing that their contemporary forms are the result of long-term political, religious, and cultural processes. The article is based on a historical analysis of the region’s history from the Middle Ages to the nineteenth century. The study shows that medieval conflicts were primarily political and dynastic rather than ethnic in character. Only the development of modern national ideologies in the eighteenth and nineteenth centuries transformed former religious and cultural communities into modern nations competing for territory, influence, and statehood. The author discusses the impact of Ottoman rule, the activities of the Churches, Russian Pan-Slavism, Greek nationalism, and Yugoslav political programs. In the conclusions, he emphasizes that contemporary Balkan conflicts do not stem solely from historical ethnic antagonisms but, above all, from modern nation-building processes and political rivalry.